Evaluation of the Wits crisis centre lay counselling training course via trainee perceptions - Arumugam, V (My University, 2016)
Abstract Keywords: Lay counsellors, training and evaluation. The training of lay counselling is of great significance to the field of Counselling Psychology. Therefore,the Health Professions Council of South Africa (HPCSA) decided to allow for the registration of lay counsellor training courses. However, the criteria for registration need to be formulated. This study evaluated the Wits Crisis course for volunteer counsellors, via illumination of the perceptions of the trainees and a measurement of their self-efficacy and personal relations before and after the training. The study included qualitative and quantitative methodology. Past trained counsellors and trainees were interviewed and then assessed on Self-Efficacy and Personal Relations before and after training. A Wilcoxon Matched-Pairs Signed-Rank significance in self-efficacy or personal relations scores after training. However, the interviews of the participants' perceptions of the course and its impact on them supported the hypotheses. Overall, perceptions were positive. Negative perceptions were highlighted, as this information could add to the knowledge base of the program.
Keywords: Counselors--Training of--South Africa; Community mental health services--South Africa .; Volunteer workers in mental health--Training of--South Africa